A Study on the Preferences of LIC Policy Holders Towards Acquisition of Policies - Pandi Kumar, M. P.; Manickavasagam, Dr. V. (Indian Journal of Finance, 2010)
The process of globalization facilitated the entire country to serve the populace in a better manner through the invasion of Structural, Legal and Financial reforms. The process of globalization has been tunneled through many stages of liberalization, in order to cater to the needs and demands of the entire country. This process of liberalization warrants many public sector undertakings to imbibe the structural changes in their fold of operations to the tune of changes in the market structure, from monopoly to perfect competition. During the process of liberalization, LIC was one of the organizations to register the changes through Malhotra committee recommendations. Though LIC is the only corporation having 52 years of insurance expertise and 11 lakh agents, it also needs to render insurance services not only to the tune of an insurance regulator, but also according to the modern practices of new entrants in the insurance industry. It is an order of the day for LIC to bring forth changes in the policy- not only in marketing the insurance schemes, but also to register the views and opinions of prospects and policy holders during the moment of sale. Since inception of LIC, the insurance market in India was driven by sale of policies out of the efforts of agents rather than purchase from the policy holders.